Reputation, policy risk, and land use: A study of China's Grain for Green programme - Haochi Zheng; Paul Glewwe; Stephen Polasky; Jintao Xu (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2011)
Since 1999, China has spent RMB 50 billion (about US7 billion) to implement the Grain for Green programme, the largest land retirement programme in the developing world. From 1999 to 2003, over 7.2 million hectares of agricultural land were retired under the programme. However, many farmers report that they did not receive the compensation promised under the programme in exchange for planting trees on their agricultural land. This paper examines the impacts of subsidy payment shortfalls, delayed payments and programme uncertainty on farmers' participation in the Grain for Green programme. A stylized reputation game is used to explain how village-level corruption (subsidy underpayment), along with uncertainty regarding the likely longevity of the programme, discourage farmers' participation in the programme. Panel data are used to estimate the impact of previous payment shortfalls on subsequent land conversion. A strong negative impact is found. Village level payment information is used to identify the impact on programme participation of both corruption and uncertainty regarding the programme's longevity. Further investigation reveals that variation in both payment receipt and programme participation appear to be driven by household specific characteristics, such as being a Communist Party member or working for the local government. These results provide useful guidance on how to make conservation efforts in developing countries more efficient and cost effective.
Keywords: D81; Q18; Q15; 330; reputation; grain for green programme; land use